Urine Neutrophil Gelatinase-associated Lipocalin and Kidney Injury in Children With Focal Segmental Glomerulosclerosis (Iranian Journal of Kidney Diseases, 2012)
Introduction. Neutrophil gelatinase-associated lipocalin (NGAL) is proposed as a marker of chronic kidney disease (CKD). This study was designed to find whether there is a correlation between urine NGAL and progression of kidney damage in children with focal segmental glomerulosclerosis (FSGS). Materials and Methods. Data were collected at the initial diagnosis of FSGS and after 12 months of treatment based on the Mendoza protocol. Twelve children with FSGS  and 15 healthy children were included. Urine NGAL was assessed at the initiation of the study in the two groups and after 1 year of receiving the treatment in the FSGS group. Results. Urine NGAL was elevated in the FSGS group (350.0 ± 67.2 ng/mL) as compared to that in the control group (9.3 ± 3.8 ng/mL; P < .001), and there was a significant decline after 1 year (180.0 ± 45.9 ng/mL) in the FSGS group (P < .001). There were significant inverse correlations between urine NGAL and estimated creatinine clearance in the FSGS patients both at diagnosis (r = -0.589, P = .03), and after 1 year (r = -0.76, P = .009). There was a significant correlation between urine NGAL and urinary protein excretion in FSGS patients at diagnosis (r = 0.628, P = .005). Conclusions. Urine NGAL in children with FSGS can be used as a marker of progression of kidney damage as expressed in its positive correlation with both declining in glomerular filtration rate and the level of proteinuria even in those with remission.